(untitled) (Research, Society and Development, 2023)
The integration of dental implants is one of the most significant advances in contemporary dentistry, revolutionizing the way we deal with tooth loss and the restoration of chewing function and aesthetics. This innovative approach involves the placement of titanium structures in the jawbone, which serve as substitutes for natural tooth roots. The success of this type of restoration depends on a crucial process: osseointegration. Objective: This study aims to carry out a narrative review of the literature on the mechanism of osseointegration of osseointegraveis implants used in dentistry in the light of the development of titanium implant surfaces routinely used in the dental clinic. Methodology: This narrative literature review research project used the PUBMED® database to search for data using the descriptors "osseointegration", "dental implants" and "implant dentistry". Results: The quality of osseointegration is of great importance to guarantee the stability of the implant and the long-term success of the treatment that will allow the implant to restore the patient’s masticatory function and aesthetics. The process of osseointegration is characterized by different sequential and interconnected phases and several factors influence success Failure in osseointegration can result in serious complications. Modern implant dentistry has revolutionized dental implants, making them a reliable and durable option for replacing missing teeth. Conclusion: Osseointegration is a well-established but constantly evolving process that continues to provide significant benefits to patients in need of oral rehabilitation.